Protocatechuic acid: A novel detoxication agent of fumonisin B1 for poultry industry - Wang, Fei; Chen, Yi; Hu, Huilong; Liu, Xinyi; Wang, Yihui; Saleemi, Muhammad Kashif; He, Cheng; Haque, Md Atiqul (Frontiers in Veterinary Science, 2022)
Fumonisin B1 (FB1) is a major fusarium mycotoxin that largely contaminates feedstuffs and foods, posing a health risk to both animals and humans. This mycotoxin can enter the human body directly through contaminated food consumption or indirectly by toxins and their metabolites. In a prior study, feed-borne FB1 is one of the leading mycotoxins in breeder eggs, leading to reduced hatchability and gizzard ulceration in chicken progenies. Currently, no effective way is available to remove FB1 from feeds and human-contaminated foods. We hypothesize that FB1 can be reduced to low risk by protocatechuic acid (PCA). To assess the ability of FB1 to be degraded in vivo, 1 ppm of FB1 was treated with PCA, or D-glucose, or silymarin, or anti-FB1 monoclonal antibody. Our study revealed that both D-glucose and PCA exhibited 53.4 and 71.43% degradation, respectively, at 80°C for 2 h, while 35.15% of FB1 detoxification was determined in the silymarin group at 60°C for 0.5 h. A dose-dependent manner was found after treatment with D-glucose or PCA at 80°C for 2 h. As for detoxification of anti-FB1 monoclonal antibody, the 1:3,000 dilution induced significant FB1 detoxification, accounting for 25.9% degradation at 25°C for 2 h. Furthermore, 50 SPF 11-day-old embryonated eggs were divided into 10 groups, with five eggs per group. Post treatment with PCA or D-glucose, or silymarin or anti-FB1 monoclonal antibody, the treated samples were inoculated into albumens and monitored daily until the hatching day. Consequently, 100% of the chickens survived in the D-glucose group and other control groups, except for the FB1 control group, while 80, 80, and 60% hatching rates were found in the PCA-treated group, the anti-FB1 monoclonal antibody-treated group, and the silymarin-treated group. Additionally, both the FB1 group and the silymarin-treated group yielded lower embryo growth than other groups did. Postmortem, lower gizzard ulceration index was determined in the PCA-treated group and the anti-FB1 monoclonal antibody-treated group compared to those of the silymarin-treated group and D-glucose-treated group. Based on the above evidence, PCA is a promising detoxification to reduce FB1 contamination in the poultry industry, contributing to the eradication of mycotoxin residuals in the food chain and maintaining food security for human beings.